Investigation of the Performance of a Sb2S3-Based Solar Cell with a Hybrid Electron Transport Layer (h-ETL): A Simulation Approach Using SCAPS-1D Software - Pierre Gérard Darel Kond Ngue; Ariel Teyou Ngoupo; Aimé Magloire Ntouga Abena; François Xavier Abomo Abega; Jean-Marie Bienvenu Ndjaka (International Journal of Photoenergy)
In order to reduce current leakage and improve electron transfer in solar cells, charge transport layers (CTL), mainly hybrid electron transport layers (h-ETL), are considered as a solution. In this research contribution, computational analysis using SCAPS-1D software is performed to explore the output photovoltaic parameters of a Sb2S3-based solar cell with h-ETL. No theoretical works on this configuration have been previously reported. The main objectives of the present work are to propose a h-ETL with good band alignment with the Sb2S3 absorber, high transparency, and Cd free; to mitigate the instability and cost issues associated with using Spiro-OMeTAD HTL; and to optimize the solar cell. Thus, we calibrated the J-V characteristics and electrical parameters of the FTO/(ZnO/TiO2)/Sb2S3/Spiro-OMeTAD/Au solar cell by numerical simulation and compared them with those of the experiment. Subsequently, our simulations show that to replace the TiO2 ETL used in the experiment and to form the h-ETL with ZnO, IGZO is found to be a good candidate. It has better band alignment with the Sb2S3 absorber than TiO2 ETL, which reduces the trap states at the ETL/Sb2S3 interface; it has high transparency due to its wide bandgap; and an intense electric field is generated at the IGZO/Sb2S3 interface, which reduces the recombination phenomenon at this interface. MoO3, MASnBr3, Cu2O, CuI, and CuSCN HTL were also tested to replace the Spiro-OMeTAD HTL. Simulation results show that the cell with MoO3 HTL achieves higher performance due to its high hole mobility and high quantum efficiency in the visible region; it also allows the solar cell to have better thermal stability (TC=−0.32%/K) than the cell with Spiro-OMeTAD HTL (TC=−0.53%/K). The parameters that could improve the solar cell efficiency (η) obtained after these substitutions were also optimized. In particular, the parameters of the Sb2S3 absorber layer (thickness, defect density, and doping), ETL and HTL layer thicknesses, h-ETL/Sb2S3 interface defect density, and series and shunt resistances have been optimized. Finally, by combining high performance and thermal stability, the results show that the thermal stability of the solar cell depends on the back contact type; thus, nickel (Ni) was found to combine high performance and better thermal stability among the back contacts investigated. After these improvements, the efficiency of the Sb2S3-based solar cell increased from 5.08% (JSC=16.19 mA/cm2, VOC=0.56 V, and FF=55.40%) to 15.43% (JSC=18.51 mA/cm2, VOC=1.11 V, and FF=74.76%). This study proposes an approach to optimize the Sb2S3 upper subcell for tandem solar cells.